Interpretational Philosophy and E. Meškauskas’ Methodology - Stoškus, Krescencijus (Problemos, 1998)
In our time philosophy like special sciences usually is being evaluated only according to its conceptual originality. But in this case whole ages (e.g., the Middle Ages, the Renaissance, even the Roman epoch) and world countries may be remained outside the field of philosophical creation. On the other hand may be impossible to explain why do the long-term philosophical tradition have residual importance. In the article are strictly separated two ways of philosophical creation - personal philosophy and interpretation philosophy. E. Meškauskas gnoseology is reviewed as sufficiently original interpretation of Marxism dialectics with is expressed in concepts of methodology, scientific character, criticism and reconstruction of reality.